Soil Profile Based Land Suitability Study for Jute and Lentil Using AHP Ranking - Singha, Chiranjit; Swain, Kishore C. (International Journal of Bio-resource and Stress Management, 2018)
The land use suitability evaluation leading to fine–tuning of crop selections and rotations are very important in optimising the land and labour productivities enhancing higher cropping intensities, producing better crop yield. The Analytical HierarchyProcess (AHP) technique coupled with GIS software environment can be a unique tool for better land suitability studies. The AHP technique is used for land suitability study in Hooghly District, West Bengal, India for existing deep rooted crops. The study area covering nearly 300 ha has been classified based on soil nutrient level with randomly selected fifty plot based soil sample analysis. The pairwise comparison matrix based ranking is carried out considering the importance of each parameter for jute and lentil crop in the region. The area, based on top soil layer could be classified as ‘highly suitable’ class of 6.5% area and ‘not suitable’ class of 2.5% area; for deep soil layer ‘highly suitable’ class occupied 10.3% of area and ‘marginal suitable’ class nearly 52.2% of area. The analysis revealed that in the study area for lentil, top layer only 3.0% classified as ‘not suitable’ but this class contribute nearly 7.2% in deep layer. The areas unsuitable for jute crop may be dedicated for lentil and other crops. This analysis will be immensely helpful for selecting tap root crops.